Manajemen Pemasaran Berbasis Media Sosial dalam Meningkatkan Daya Saing Lembaga Pendidikan di Era Digital - Afina Mazaya Auliya Mida; Naila Wildatun Isanaini; Najwa Kamila; Renata Fifa Aulia (Jurnal Cakrawala Pendidikan dan Biologi, 2026)
Digital transformation has shifted the marketing paradigm of educational institutions from conventional approaches to social media-based strategies. This study aims to analyze the implementation of social media-based marketing management as a strategic tool for enhancing the competitiveness of educational institutions in the digital age. The study focuses on three main aspects: the formulation of digital marketing management strategies, the integrated application of the 7P service marketing mix through social media platforms, and its impact on institutional competitiveness. This study used a systematic literature review by examining relevant scientific publications, books, and previous research related to educational marketing, social media management, and institutional competitiveness. The results indicate that well-planned and professional social media management can increase the number of student applicants, strengthen brand awareness, expand communication reach, and build public trust in the institution. Social media also enables schools to present academic programs, institutional achievements, facilities, and educational values more interactively. However, limited digital literacy, human resource capacity, content consistency, and technological infrastructure remain structural barriers that need to be addressed systematically through training, policy support, and sustainable digital innovation practices.